Sodium-electrode layered oxide positive electrode material and preparation method thereof, positive electrode plate, battery and electric device
By uniformly mixing O3 phase and P2 phase particles in the sodium-electric layered oxide positive electrode material, adjusting their synergistic effects under different voltage conditions, the problem of poor structural stability of the material during high-deep discharge is solved, and the comprehensive performance of high energy density, wide voltage interval discharge stability and long cycle life is achieved.
Patent Information
- Application Number
- CN202411892257.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing sodium-electric layered oxide positive electrode materials have poor structural stability during high-deep discharge, resulting in deterioration of cyclic performance, and are unable to achieve high energy density, wide voltage interval discharge stability and long cycle life at the same time.
By uniformly mixing the Class I particles of O3 phase and the Class II particles of P2 phase, their synergistic effects under different voltage conditions are adjusted to optimize the structure and electrochemical properties of the material. The specific method includes adjusting the phase structure and mass proportion of the particles according to the X-ray powder diffraction pattern, and preparing the positive electrode material through a segmented sintering and dry mixing process.
The sodium-electric layered oxide positive electrode material has high structural stability during high-deep discharge, and has high energy density, wide voltage range (1.5~4.2V) discharge stability and long cycle life.
Smart Images

Figure CN119852388A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium-ion layered oxide positive electrode material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] Sodium-ion batteries are considered to be another rechargeable battery technology suitable for large-scale commercialization besides lithium-ion batteries due to their advantages in safety and cost. In sodium-ion batteries, layered oxide cathode materials are valued for their high energy density, fast sodium ion movement speed, simple manufacturing process and low cost.
[0003] The commonly used layered oxide positive electrode materials for sodium-ion batteries mainly include O3 structure and P2 structure. The sodium-ion layered oxide positive electrode material with O3 structure can release more sodium ions and has a higher theoretical energy capacity, but during the charge and discharge process, the O3 structure material will undergo complex phase changes, especially irreversible phase changes at high voltages, which will seriously affect the cycle life and rapid charge and discharge performance. In contrast, the sodium layered oxide positive electrode material with P2 structure has a larger sodium interlayer spacing, which is conducive to the movement of sodium ions and has better high-voltage stability, but due to the lower sodium content, its theoretical capacity and actual capacity are significantly lower than those of the sodium-ion layered oxide positive electrode material with O3 structure.
[0004] Some studies have proposed P and O mixed phase materials (P / O structure), using the synergistic effect of the two phases to alleviate or inhibit the structural phase change at high voltage, thereby improving the electrochemical performance of the material. However, O3, P2, and P / O structures cannot solve the stability problem of high depth discharge. When the discharge cut-off voltage is <2V, a large amount of Mn 4+ Reduced to Mn 3+ , which makes the material structure stability worse, metal dissolution intensifies, and cycle performance deteriorates, that is, the discharge specific capacity and discharge voltage are significantly attenuated. Therefore, the current sodium layered oxide positive electrode materials have failed to solve the key problems of high specific energy, high cycle stability, and discharge stability in a wide voltage range. Summary of the invention
[0005] The purpose of the present invention is to provide a sodium layered oxide positive electrode material and a preparation method, a positive electrode sheet, a battery and an electrical device to solve the problems existing in the background technology.
[0006] The technical scheme of the present invention comprises: a sodium-electrode layered oxide positive electrode material, wherein the sodium-electrode layered oxide positive electrode material comprises a uniform mixture of type I particles and type II particles, and the phase structures of the type I particles and the type II particles are different; in an X-ray powder diffraction spectrum measured using Cu-Kα rays, the uniform mixture has at least: a diffraction peak P corresponding to a (003) crystal plane at 2θ of 15° to 18°; γ and the diffraction peak P corresponding to the (002) crystal plane φ , diffraction peak P γ The diffraction angle is γ and the peak intensity is I γ , diffraction peak P φ The diffraction angle is φ and the peak intensity is I φ ,φ<γ,
[0007] Further, in each X-ray powder diffraction pattern measured using Cu-Kα radiation, at 2θ of 15° to 18°:
[0008] The type I particles have a diffraction peak P corresponding to the (003) crystal plane. δ , diffraction peak P δ The diffraction angle is δ and the peak intensity is I δ ;
[0009] The type II particles at least have a diffraction peak P corresponding to the (002) crystal plane. ε , diffraction peak P ε The diffraction angle is ε and the peak intensity is I ε ;
[0010] ε<δ, w is the mass proportion of the type I particles in the homogeneous mixture.
[0011] Furthermore, the chemical formula of the Class I particles is Na x1 Ni a1 Mn b1 M y1 O 2 The chemical formula of the type II particles is Na x2 Ni a2 Mn b2 M y2 O 2 ,in:
[0012] 0.6 <x2<0.9<x1<1.1,0.3<b1<b2<1,x1·w+x2·(1-w)> 0.9.
[0013] Furthermore, M in the chemical formula of the Class I particles and the chemical formula of the Class II particles are independently selected from one or more of Fe, Cu, Li, Mg, Al, Ca, Cu, Zn, Ti, Zr, Cr, Sr, Ba, Nb, Mo and W, and a1+b1+y1=1, a2+b2+y2=1.
[0014] Furthermore, when n moles of sodium ions are released per mole of the Class I particles based on metallic sodium, the potential is U Ⅰ When each mole of the type II particles releases n moles of sodium ions based on metallic sodium, its potential is U Ⅱ , for any n≤0.5, U Ⅰ <U Ⅱ ;
[0015] In a sodium ion battery containing the sodium-ion layered oxide positive electrode material, the sodium ion battery is discharged to U 放电截止 When the valence state of Mn in the type I particles is V Ⅰ The valence state of Mn in the type II particles is V Ⅱ , 1.5V≤U 放电截止 ≤2V, 3.5<V Ⅱ <V Ⅰ <4.0.
[0016] The technical solution of the present invention also includes: a method for preparing the sodium layered oxide positive electrode material as described above, which comprises the steps of:
[0017] According to the molar ratio of elements in the type I particles and the type II particles, a sodium source, a nickel source, a manganese source and an M source are taken to obtain type I raw materials and type II raw materials respectively;
[0018] The Class I raw materials and the Class II raw materials are sintered, crushed, and screened in stages to obtain Class I particles and Class II particles;
[0019] The type I particles and the type II particles are mixed in a certain ratio to obtain a sodium-based layered oxide positive electrode material.
[0020] Further, in the preparation method:
[0021] The sodium source includes at least one of sodium carbonate and sodium bicarbonate;
[0022] The nickel source, manganese source and M source respectively include at least one of oxides, hydroxides, chlorides and carbonates containing corresponding metal elements;
[0023] The conditions for staged sintering are: first calcining at 500°C for 1 to 10 hours, then calcining at 850 to 1100°C for 6 to 30 hours, and finally cooling with the furnace. During the cooling process, the relative humidity of the environment is ≤30%.
[0024] During the process of crushing, screening and mixing of Class I and Class II particles, the relative humidity of the environment is ≤20%.
[0025] The technical solution of the present invention also includes: a positive electrode plate, wherein the positive electrode plate contains the sodium-electrolyte layered oxide positive electrode material as described above.
[0026] The technical solution of the present invention also includes: a battery, wherein the battery contains the positive electrode plate as described above.
[0027] The technical solution of the present invention also includes: an electrical device, wherein the electrical device contains the battery as described above.
[0028] The present invention has the following beneficial effects: the sodium-based layered oxide positive electrode material provided by the present invention achieves optimization of the structure and electrochemical performance by adjusting the sodium and manganese content in the type I particles and the type II particles and the ratio of the two types of particles, improves the synergistic effect of the two under different voltage conditions, and thus ensures that the sodium-based layered oxide positive electrode material with high energy density has high structural stability during the entire process of high-depth discharge, so that it has the performance of high energy density, high discharge stability in a wide voltage range (1.5 to 4.2 V), and high cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is the XRD pattern of the sodium-electrode layered oxide positive electrode material prepared in Example 1 of the present invention;
[0030] Figure 2 The charge and discharge curves of the type I particles, type II particles and sodium layered oxide positive electrode materials prepared in Example 1;
[0031] Figure 3 The battery cycle performance comparison diagram of the sodium layered oxide positive electrode materials prepared in Examples 1-6 at 1.5V to 4.2V;
[0032] Figure 4 This is a comparison chart of the battery cycle performance of the sodium battery positive electrode materials prepared in Comparative Examples 1-6 at 1.5V to 4.2V. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with embodiments and accompanying drawings:
[0034] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and comparative examples, and are not intended to limit the scope of protection of the present invention. It should be particularly noted that there may be multiple names for the same organic structure, as long as the structure is within the scope of this patent, it belongs to the protection object of this patent.
[0035] Unless otherwise defined, the raw materials, reagents, etc. in the following examples can be purchased from the market or prepared according to reported methods.
[0036] In the first aspect of the present invention, a sodium-electric layered oxide positive electrode material is proposed. According to an embodiment of the present invention, the sodium-electric layered oxide positive electrode material is a uniform mixture of Class I particles and Class II particles, the phase structures of Class I particles and Class II particles are different, Class I particles are O3 phase, Class II particles contain at least P2 phase, and may also contain part of P / O phase; in the sodium-electric layered oxide positive electrode material, the mass proportion of Class I particles is w, and the mass proportion of Class II particles is 1-w; in the respective X-ray powder diffraction patterns measured using Cu-Kα rays, at 2θ of 15° to 18°:
[0037] (1) Type I particles have a diffraction peak P corresponding to the (003) crystal plane. δ , diffraction peak P δ The diffraction angle is δ and the peak intensity is I δ ;
[0038] (2) Type II particles have at least one diffraction peak P corresponding to the (002) crystal plane. ε , diffraction peak P ε The diffraction angle is ε and the peak intensity is I ε , there may be a diffraction peak P' corresponding to the (003) crystal plane (the corresponding peak intensity is I');
[0039] (3) The sodium layered oxide positive electrode material has a diffraction peak P corresponding to the (003) crystal plane. γ and the diffraction peak P corresponding to the (002) crystal plane φ , diffraction peak P γ The diffraction angle is γ and the peak intensity is I γ , diffraction peak P φ The diffraction angle is φ and the peak intensity is I φ ;
[0040] Among them, ε<δ, φ<γ,
[0041] In this embodiment, the type I particles mainly contribute the O3 phase structure to the sodium-electrode layered oxide positive electrode material, so that the sodium-electrode layered oxide positive electrode material has a diffraction peak corresponding to the (003) crystal plane in the XRD spectrum, and the type I particles can release more sodium ions, so that the sodium-electrode layered oxide positive electrode material has a higher theoretical capacity; the type II particles mainly contribute the P2 phase structure to the sodium-electrode layered oxide positive electrode material, and may contribute a small amount of P / O phase structure, so that the sodium-electrode layered oxide positive electrode material has a diffraction peak corresponding to the (002) crystal plane in the XRD spectrum, and may increase the peak intensity of the diffraction peak corresponding to the (003) crystal plane in the XRD spectrum of the sodium-electrode layered oxide positive electrode material, that is, In addition, Type II particles have more sodium ion vacancies and larger sodium layer spacing, which is conducive to the movement of sodium ions and improves the rapid charge and discharge performance of sodium-electrolyte layered oxide positive electrode materials.
[0042] In addition, the inventors of the present technical solution also found in their research that during the charge and discharge process, the type I particles that mainly contribute to the O3 phase structure will undergo a complex phase transition, mainly including O3 phase → monoclinic O'3 phase → P3 phase → O phase. + ), the sodium interlayer spacing will decrease sharply during the evolution of P3 phase → O phase, and the phase transition reversibility is extremely poor, which seriously affects the cycle life and rapid charge and discharge performance of the material. The type II particles that mainly contribute to the P2 phase structure show obvious hysteresis when de-sodiumizing at high voltage, and thus show good high-voltage stability. The existence of type II particles can alleviate or inhibit the trend of irreversible phase transition of type I particles at high voltage, and improve the structural stability of sodium-based layered oxide positive electrode materials at high voltage; when the discharge cut-off voltage is less than 2V, the type II particles that mainly contribute to the P2 phase structure (partial P / O phase structure may exist) have sodium ion vacancies, and the sodium ions are re-embedded in the sodium ion vacancies of the type II particles to form a sodium-rich phase, accompanied by the Mn 4+ Reduced to Mn 3+ , Mn 3+ The Jan-Taylor effect makes the material structure stability worse, metal dissolution intensifies, and the cycle performance deteriorates. When it exists in Type I particles, it can reduce the over-embedding phenomenon of sodium ions in Type II particles at low discharge voltage by accepting some sodium ions, thereby improving the structural stability of sodium-based layered oxide positive electrode materials at low discharge voltage.
[0043] The inventors of this technical solution also found in their research: It can effectively ensure that the sodium-ion vacancy concentration in the sodium-electrolyte layered oxide positive electrode material is appropriate, and a higher platform voltage and energy density retention capability during a long cycle can be achieved; when When , the proportion of type II particles with high sodium ion vacancy concentration in the sodium-electrolyte layered oxide positive electrode material is relatively small, which is not conducive to improving the platform voltage of the material, and the high voltage stability of the material becomes worse; when When the sodium ion content of type I particles is high, the proportion of type I particles in the sodium-electrolyte layered oxide positive electrode material is relatively small, the material capacity is inhibited, and the stability of the material during high depth discharge becomes poor.
[0044] The sodium layered oxide positive electrode material that meets the above conditions provided in this embodiment utilizes the differences in structure and electrochemical properties between Class I particles and Class II particles, and adjusts the mass ratio of Class I particles and Class II particles to improve the synergistic effect of the two under different voltage conditions, thereby ensuring that the sodium layered oxide positive electrode material with high energy density has high structural stability throughout the entire process of high depth discharge, so that it has high energy density, high discharge stability in a wide voltage range (1.5~4.2V), and high cycle life.
[0045] According to the findings of the inventors of the present technical solution in their research: the content of sodium and manganese in the material components determines the number of sodium ions that can be inserted and removed and the content of sodium ion vacancies in the material, and the content of sodium ion vacancies affects the spacing between the (003) crystal plane and the (002) crystal plane. At the same time, from the perspective of charge balance, the concentration of sodium ion vacancies is also accompanied by changes in the valence state of manganese ions. Through experiments, exploration and research, it is determined that the chemical formula of the Class I particles in this embodiment is Na x1 Ni a1 Mn b1 M y1 O 2 The chemical formula of type II particles is Na x2 Ni a2 Mn b2 M y2 O 2 , wherein M in the two chemical formulas is independently selected from one or more of Fe, Cu, Li, Mg, Al, Ca, Cu, Zn, Ti, Zr, Cr, Sr, Ba, Nb, Mo and W, a1+b1+y1=1, a2+b2+y2=1, 0.6 <x2<0.9<x1<1.1,0.3<b1<b2<1,x1·w+x2·(1-w)> 0.9.
[0046] Among them, x1·w+x2·(1-w)>0.9 can effectively ensure that there are sufficient sodium ions in the sodium-electrolyte layered oxide positive electrode material to achieve high specific capacity; the appropriately added M element helps to further improve the structural stability of the material and improve the comprehensive electrical properties of the material.
[0047] In order to further optimize the electrochemical performance of sodium-electrolyte layered oxide positive electrode materials, the inventors of the present technical solution conducted in-depth research and found that among the Class I particles, Class II particles and sodium-electrolyte layered oxide positive electrode materials that meet the above conditions, when the following conditions are met: when each mole of Class I particles releases n moles of sodium ions based on metallic sodium, its potential is U Ⅰ When each mole of the type II particles releases n moles of sodium ions based on metallic sodium, its potential is U Ⅱ , for any n≤0.5, U Ⅰ <U Ⅱ This can ensure that Class II particles have obvious hysteresis when sodium ions are released compared to Class I particles, and exhibit good high-voltage stability, thereby providing effective capacity in the high-voltage range while alleviating the irreversible structural changes of Class I particles under high-voltage and high-SOC conditions.
[0048] In order to further optimize the electrochemical performance of the sodium-ion layered oxide positive electrode material, the inventors of the present technical solution conducted in-depth research and found that among the Class I particles, Class II particles and sodium-ion layered oxide positive electrode materials that meet the above conditions, when the following conditions are met: in a sodium-ion battery containing the sodium-ion layered oxide positive electrode material, the sodium-ion battery is discharged to U 放电截止 When the valence state of Mn in type I particles is V Ⅰ , the valence state of Mn in type II particles is V Ⅱ , 1.5V≤U 放电截止 ≤2V, 3.5<V Ⅱ <V Ⅰ <4.0, which can ensure that during high depth discharge, the type II particles will not be over-embedded with sodium ions, reduce the content of +3-valent manganese ions in the type II particles, improve the stability of the crystal structure, and ensure the stability of the platform voltage during the cycle.
[0049] It is worth noting that the above I δ ,I ε ,I γ and I φ All are normalized diffraction peak intensities.
[0050] The second aspect of the present invention provides a method for preparing the sodium layered oxide positive electrode material described in the first aspect. The preparation method provided in this embodiment comprises the following steps:
[0051] (1) taking a sodium source, a nickel source, a manganese source and an M source according to the molar ratio of the elements in the type I particles and the type II particles to obtain type I raw materials and type II raw materials respectively;
[0052] In this step, the sodium source includes at least one of sodium carbonate and sodium bicarbonate, and the nickel source, manganese source and M source respectively include at least one of oxides, hydroxides, chlorides and carbonates containing corresponding metal elements.
[0053] (2) sintering, crushing, and screening the Class I raw materials and Class II raw materials in stages to obtain Class I particles and Class II particles;
[0054] In this step, the conditions for staged sintering are: first calcining at 500°C for 1 to 10 hours, then calcining at 850 to 1100°C for 6 to 30 hours, and finally cooling with the furnace. During the cooling process, the relative humidity of the environment is ≤30%; during the crushing and screening process, the relative humidity of the environment is ≤20%.
[0055] (3) The type I particles and the type II particles are mixed in a certain ratio to obtain a sodium layered oxide positive electrode material.
[0056] In this step, when mixing according to the ratio, dry mixing is adopted, and the relative humidity of the environment is ≤20%.
[0057] By controlling the relative humidity of the environment in the above steps (2) and (3), it is helpful to reduce the moisture in the type I particles, type II particles and sodium layered oxide positive electrode materials, and avoid water molecules from being embedded in the material layers and damaging the material structure. In addition, the dry mixing process is simple and fully compatible with the existing positive electrode material production process.
[0058] The third aspect of the present invention provides a positive electrode sheet, which contains the sodium-electrolyte layered oxide positive electrode material described in the first aspect.
[0059] The fourth aspect of the present invention provides a battery, which contains the positive electrode sheet described in the third aspect.
[0060] The fifth aspect of the present invention provides an electrical device comprising the battery described in the fourth aspect.
[0061] The present invention will be described in detail below through examples and comparative examples.
[0062] Example 1
[0063] (1) taking a sodium source, a nickel source, a manganese source and an M source according to the molar ratio of the elements in the type I particles and the type II particles to obtain type I raw materials and type II raw materials respectively;
[0064] In this step, the sodium source in the type I particles is Na 2 CO 3 , nickel source is NiO, manganese source is Mn 2 O 3 、M source is Fe 2 O 3 The molar ratio of elements in the Class I particles is: Na:Ni:Mn:Fe=3:1:1:1; after use, they are mixed evenly in a high-speed mixer to obtain Class I raw materials;
[0065] In this step, the sodium source in the type II particles is Na 2 CO 3 , nickel source is NiO, manganese source is Mn 2 O 3 、M source is Fe 2 O 3 The molar ratio of elements in the Class II particles is: Na:Ni:Mn:Fe=0.80:0.20:0.50:0.30; after use, they are mixed evenly in a high-speed mixer to obtain Class II raw materials.
[0066] (2) sintering, crushing, and screening the Class I raw materials and Class II raw materials in stages to obtain Class I particles and Class II particles;
[0067] In this step, the conditions for the staged sintering of Class I raw materials are: first calcining at 500°C for 4 hours, then calcining at 950°C for 24 hours, and finally cooling with the furnace. The relative humidity of the environment during the cooling process is 20%; during the crushing and screening process, the relative humidity of the environment is 15%; finally, the chemical formula of NaNi 1 / 3 Mn 1 / 3 Fe 1 / 3 O 2 Type I particles;
[0068] In this step, the conditions for the staged sintering of the Class II raw materials are: first calcining at 500°C for 4 hours, then calcining at 950°C for 24 hours, and finally cooling with the furnace. The relative humidity of the environment during the cooling process is 20%; during the crushing and screening process, the relative humidity of the environment is 15%; finally, the chemical formula of Na 0.80 Ni 0.20 Mn 0.50 Fe 0.30 O 2 Type II particles.
[0069] (3) The type I particles and the type II particles are mixed in a certain ratio to obtain a sodium layered oxide positive electrode material.
[0070] In this step, the mass ratio of Class I particles to Class II particles is 750:250; when mixing according to the ratio, the particles are mixed evenly by a VC high-speed mixer, and the relative humidity of the environment is controlled at 20%.
[0071] Example 2
[0072] The only difference from Example 1 is that in step (3) of Example 2: the mass ratio of Class I particles to Class II particles is 600:400; when mixing according to the ratio, the mixture is mixed evenly by a VC high-speed mixer, and the relative humidity of the environment is controlled at 15%.
[0073] Example 3
[0074] The only difference from Example 1 is that in step (3) of Example 3: the mass ratio of Class I particles to Class II particles is 900:100; when mixing according to the ratio, the mixture is mixed evenly by a VC high-speed mixer, and the relative humidity of the environment is controlled at 15%.
[0075] Example 4
[0076] The only difference from Example 1 is that in steps (1) and (2) of Example 4: the raw material used to prepare Class I particles is Na 2 CO 3 、Ni 1 / 3 Mn 1 / 3 Fe 1 / 3 (OH) 2 The raw material used to prepare type II particles is Na 2 CO 3 、Ni 0.2 Mn 0.5 Fe 0.3 (OH) 2 ; The chemical formula of Class I particles and Class II particles is the same as that in Example 1.
[0077] Example 5
[0078] The only difference from Example 1 is that in steps (1) and (2) of Example 5: the raw material used to prepare Class I particles is NaHCO 3 、Ni(OH) 2 、MnCO 3 、FeCl 3 The raw material used to prepare type II particles is NaHCO 3 、Ni(OH) 2 、MnCO 3 、FeCl 3 ; The chemical formula of Class I particles and Class II particles is the same as that in Example 1.
[0079] Example 6
[0080] (1) taking a sodium source, a nickel source, a manganese source and an M source according to the molar ratio of the elements in the type I particles and the type II particles to obtain type I raw materials and type II raw materials respectively;
[0081] In this step, the sodium source in the type I particles is Na 2 CO 3 , nickel source is NiO, manganese source is Mn 2 O 3 , M source is CuO and TiO 2 The molar ratio of elements in the Class I particles is: Na:Ni:Mn:Cu:Ti=0.95:0.40:0.40:0.10:0.10; after use, mix them evenly in a high-speed mixer to obtain Class I raw materials;
[0082] In this step, the sodium source in the type II particles is Na 2 CO 3 , nickel source is NiO, manganese source is Mn 2 O 3 、M source is LiOH, MgCO 3 The molar ratio of elements in the Class II particles is: Na:Ni:Mn:Li:Mg=0.65:0.20:0.60:0.10:0.10; after use, mix them evenly in a high-speed mixer to obtain Class II raw materials.
[0083] (2) sintering, crushing, and screening the Class I raw materials and Class II raw materials in stages to obtain Class I particles and Class II particles;
[0084] In this step, the conditions for the staged sintering of Class I raw materials are: first calcining at 500°C for 4 hours, then calcining at 1000°C for 24 hours, and finally cooling with the furnace. The relative humidity of the environment during the cooling process is 20%; the relative humidity of the environment during the crushing and screening process is 30%; finally, the chemical formula of Na 0.95 Ni 0.40 Mn 0.40 Cu 0.10 Ti 0.10 O 2 Type I particles;
[0085] In this step, the conditions for the staged sintering of the Class II raw materials are: first calcining at 500°C for 4 hours, then calcining at 950°C for 24 hours, and finally cooling with the furnace. The relative humidity of the environment during the cooling process is 20%; during the crushing and screening process, the relative humidity of the environment is 15%; finally, the chemical formula of Na 0.65 Ni 0.20 Mn 0.60 Li 0.10 Mg 0.10 O 2 Type II particles.
[0086] (3) The type I particles and the type II particles are mixed in a certain ratio to obtain a sodium layered oxide positive electrode material.
[0087] In this step, the mass ratio of Class I particles to Class II particles is 750:250; when mixing according to the ratio, the particles are mixed evenly by a VC high-speed mixer, and the relative humidity of the environment is controlled at 20%.
[0088] Comparative Example 1
[0089] The sodium battery positive electrode material of Comparative Example 1 only contains Type I particles prepared in Example 1.
[0090] Comparative Example 2
[0091] The sodium battery positive electrode material of Comparative Example 2 only contains the Type II particles prepared in Example 1.
[0092] Comparative Example 3
[0093] The only difference compared with Example 1 is that in step (3) of Comparative Example 3: the mass ratio of Class I particles to Class II particles is 950:50.
[0094] Comparative Example 4
[0095] The only difference compared with Example 1 is that the material collection principle followed in steps (1) and (2) of Comparative Example 4 and the materials obtained all meet the following requirements: The chemical formula of Class I particles is Na 0.83 Ni 1 / 3 Mn 1 / 3 Fe 1 / 3 O 2 .
[0096] Comparative Example 5
[0097] The only difference compared with Example 1 is that the material collection principle followed in steps (1) and (2) of Comparative Example 5 and the materials obtained all meet the following requirements: The chemical formula of Class II particles is NaNi 0.2 Mn 0.5 Fe 0.3 O 2 .
[0098] Comparative Example 6
[0099] The only difference compared with Example 1 is that the material collection principle followed in steps (1) and (2) of Comparative Example 6 and the materials obtained all meet the following requirements: The chemical formula of Class I particles is NaNi 0.2 Mn 0.5 Fe 0.3 O 2 .
[0100] The present invention uses the following method to conduct physical and chemical characterization tests on the sodium-based layered oxide positive electrode materials, Class I particles or Class II particles prepared in Examples 1-6, and the sodium-based positive electrode materials, Class I particles or Class II particles prepared in Comparative Examples 1-6 (hereinafter referred to as samples) and obtain corresponding test results.
[0101] (1) ICP test: The sample was dissolved in hydrochloric acid and prepared into a solution of a certain concentration. The content and chemical formula composition of the metal elements in the sample were tested by inductively coupled plasma atomic emission spectrometry. The results are shown in Table 1.
[0102] Table 1ICP test results
[0103] Sample source x1 x2 b1 b2 w Example 1 1.0 0.80 1 / 3 0.50 75% Example 2 1.0 0.80 1 / 3 0.50 60% Example 3 1.0 0.80 1 / 3 0.50 90% Example 4 1.0 0.80 1 / 3 0.50 75% Example 5 1.0 0.80 1 / 3 0.50 75% Example 6 0.95 0.65 0.4 0.6 75% Comparative Example 1 1.0 — 1 / 3 — 100% Comparative Example 2 — 0.80 — 0.50 0% Comparative Example 3 1.0 0.80 1 / 3 0.50 95% Comparative Example 4 0.83 0.80 1 / 3 0.50 75% Comparative Example 5 1.0 1.0 1 / 3 0.50 75% Comparative Example 6 1.0 0.80 0.50 0.50 75%
[0104] (2) XRD test: Cu-Kα target was used, emission wavelength λ = 0.154 nm, scanning voltage was 40 kV, current was 40 mA, step scanning mode was used, scanning range was 10° to 90°, the results are shown in Table 2 and Table 3. Among them, the XRD spectrum of the sodium layered oxide positive electrode material prepared in Example 1 is shown in Figure 1 As shown, it has excellent crystallinity, and there are two diffraction peaks in the range of 2θ=15°~18°, and γ and φ correspond to the (003) crystal plane of type I particles and the (002) crystal plane of type II particles, respectively.
[0105] Table 2 XRD test results-1
[0106]
[0107] Table 3 XRD test results-2
[0108]
[0109]
[0110] (3) Electrochemical performance test and element valence test after discharge
[0111] The specific preparation method of the sodium secondary battery and its positive electrode sheet is as follows: the sample is mixed with acetylene black, carbon nanotubes, and polyvinylidene fluoride in a mass ratio of 90:5:1:4, and an appropriate amount of N-methylpyrrolidone is added as a dispersant, and ground into a slurry; then the slurry is evenly coated on the single side surface of the aluminum foil, vacuum dried at 120°C for 10 hours, the dried electrode sheet is rolled with a roller machine, and the aluminum foil is cut with a slicer to cut into a circular electrode sheet with a diameter of 1.3 cm, and the loading amount of the active material is controlled at 10 mg cm -2 About. The half-cell was assembled in an argon atmosphere glove box, with a water partial pressure of ≤0.1ppm and an oxygen partial pressure of ≤0.1ppm. Metallic sodium was used as the counter electrode, 1M NaPF6 (EC / DEC, volume ratio of 1:1) solution was used as the electrolyte, and a button cell of CR2032 type was assembled.
[0112] (3.1) Electrode potential test method under different sodium ion release amounts: The button cell containing Class I particles or Class II particles was charged at room temperature using a constant current charge and discharge mode. According to the charge specific capacity C = n·26800 / Mr, where Mr is the molar mass of Class I particles or Class II particles, taking n = 0.1, 0.3, and 0.5 as examples, the C values of different charge specific capacities were obtained. The cells were charged at a current density of 15 mA / g to the above different specific capacities, and the corresponding cutoff potential U was recorded. The results are shown in Table 4.
[0113] Table 4 Electrode potential test results
[0114]
[0115]
[0116] (3.2) Sodium ion battery capacity and cycle test method: The button cell was charged and discharged at room temperature using a constant current charge and discharge mode. First, the constant current was charged to 4.2 V (vs. Na / Na) at a current density of 15 mA / g. + ), and then discharged at a constant current density of 15 mA / g to 1.5 V (vs. Na / Na + ) to obtain the gram capacity and first cycle coulombic efficiency of the material. The cycle test is to use the constant current charge and discharge mode to perform 100 cycles of charge and discharge at room temperature and record the discharge specific energy of the material. The voltage range is 1.5V~4.2V and the current density is 50m·g -1 , the test results refer to Table 5 and Appendix Figure 2-4 .
[0117] Table 5 Battery capacity and cycle performance test results
[0118]
[0119] (3.3) XPS test: By testing the value and change of photoelectron kinetic energy / binding energy, the elements on the surface of the material after the discharge in (3.2) were analyzed. The obtained data were fitted using Casa XPS software to analyze the chemical valence state of the material and the proportion of elements in different valence states. The results are shown in Table 6.
[0120] Table 6 Test results of Mn element valence
[0121]
[0122]
[0123] Referring to the test results of Comparative Examples 4-6, when the sodium-manganese ratio in Class I particles and Class II particles changes, the diffraction peak of the sample at 2θ of 15° to 18° changes significantly (Table 1-3), and the material appears a heterogeneous phase caused by structural distortion; due to the change in the structure of the sample, the cut-off voltage under different sodium ion release amounts changes significantly during the charging process. Under the same sodium ion release amount (n≤0.5), the potential U of Class II particles appears. Ⅱ <The potential U of type I particles Ⅰ(Table 4), or the case where the valence of Mn in the sample at the end of high depth discharge is lower than 3.5 (Table 6). The former shows that the hysteresis of type II particles compared with type I particles in the release of sodium ions disappears, and it is difficult to achieve the synergistic effect of the two types of particles under high voltage. The latter shows that the stability of the material structure has deteriorated significantly, and it shows obvious cyclic energy attenuation at high depth discharge (Table 5).
[0124] Referring to the test results of Comparative Examples 1-3, when the ratio of type I particles and type II particles in the sodium positive electrode material changes, The key control parameters such as MgO2 and MgO2 exceeded the specified range, resulting in the lack of synergistic effect between the two types of particles in the sodium battery positive electrode material. The coulombic efficiency in the first week was significantly reduced, and the long cycle performance in the wide voltage range of 1.5V to 4.2V also deteriorated sharply (Table 5).
[0125] The sodium-electrolyte layered oxide positive electrode material provided by the present invention achieves optimization of structure and electrochemical performance by adjusting the sodium and manganese content in Class I particles and Class II particles and the ratio of the two types of particles, improves the synergistic effect of the two under different voltage conditions, and thus ensures that the sodium-electrolyte layered oxide positive electrode material with high energy density has high structural stability in the whole process of high depth discharge, so that it has high energy density, high discharge stability in a wide voltage range (1.5-4.2V), high cycle life and other performances.
[0126] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A sodium layered oxide positive electrode material, characterized in that: The sodium layered oxide positive electrode material comprises a uniform mixture of type I particles and type II particles, wherein the type I particles and the type II particles have different phase structures; in an X-ray powder diffraction spectrum measured using Cu-Kα rays, the uniform mixture has at least: a diffraction peak P corresponding to the (003) crystal plane at 2θ of 15° to 18°; γ and the diffraction peak P corresponding to the (002) crystal plane φ , diffraction peak P γ The diffraction angle is γ and the peak intensity is I γ , diffraction peak P φ The diffraction angle is φ and the peak intensity is I φ ,φ<γ, 2. The sodium layered oxide positive electrode material according to claim 1, characterized in that: In the respective X-ray powder diffraction patterns measured using Cu-Kα radiation, at 2θ of 15° to 18°: The type I particles have a diffraction peak P corresponding to the (003) crystal plane. δ , diffraction peak P δ The diffraction angle is δ and the peak intensity is I δ ; The type II particles at least have a diffraction peak P corresponding to the (002) crystal plane. ε , diffraction peak P ε The diffraction angle is ε and the peak intensity is I ε ; w is the mass proportion of the type I particles in the homogeneous mixture.
3. The sodium layered oxide positive electrode material according to claim 1 or 2, characterized in that: The chemical formula of the Class I particles is Na x1 Ni a1 Mn b1 M y1 O2, the chemical formula of the type II particles is Na x2 Ni a2 Mn b2 M y2 O2, where: 0.6 <x2<0.9<x1<1.1,0.3<b1<b2<1,x1·w+x2·(1-w)> 0.
9.
4. The sodium layered oxide positive electrode material according to claim 3, characterized in that: The M in the chemical formula of the Class I particles and the chemical formula of the Class II particles are independently selected from one or more of Fe, Cu, Li, Mg, Al, Ca, Cu, Zn, Ti, Zr, Cr, Sr, Ba, Nb, Mo and W, and a1+b1+y1=1, a2+b2+y2=1.
5. The sodium layered oxide positive electrode material according to any one of claims 2 to 4, characterized in that: When each mole of the Class I particles releases n moles of sodium ions based on metallic sodium, its potential is U Ⅰ When each mole of the type II particles releases n moles of sodium ions based on metallic sodium, its potential is U Ⅱ , for any n≤0.5, U Ⅰ <U Ⅱ ; In a sodium ion battery containing the sodium-ion layered oxide positive electrode material, the sodium ion battery is discharged to U 放电截止 When the valence state of Mn in the type I particles is V Ⅰ The valence state of Mn in the type II particles is V Ⅱ , 1.5V≤U 放电截止 ≤2V, 3.5<V Ⅱ <V Ⅰ <4.
0.
6. A method for preparing a sodium layered oxide positive electrode material according to any one of claims 2 to 5, characterized in that: Includes steps: According to the molar ratio of elements in the type I particles and the type II particles, a sodium source, a nickel source, a manganese source and an M source are taken to obtain type I raw materials and type II raw materials respectively; The Class I raw materials and the Class II raw materials are sintered, crushed, and screened in stages to obtain Class I particles and Class II particles; The type I particles and the type II particles are mixed in a certain ratio to obtain a sodium-based layered oxide positive electrode material.
7. The method for preparing a sodium-electrolyte layered oxide positive electrode material according to claim 6, characterized in that: The sodium source includes at least one of sodium carbonate and sodium bicarbonate; The nickel source, manganese source and M source respectively include at least one of oxides, hydroxides, chlorides and carbonates containing corresponding metal elements; The conditions for staged sintering are: first calcining at 500°C for 1 to 10 hours, then calcining at 850 to 1100°C for 6 to 30 hours, and finally cooling with the furnace. During the cooling process, the relative humidity of the environment is ≤30%. During the process of crushing, screening and mixing of Class I and Class II particles, the relative humidity of the environment is ≤20%.
8. A positive electrode sheet, characterized in that: The positive electrode sheet contains the sodium-electrolyte layered oxide positive electrode material described in any one of claims 1-5.
9. A battery, characterized in that The battery contains the positive electrode sheet according to claim 8.
10. An electrical device, characterized in that: The electrical device contains the battery according to claim 9.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material, preparation method and application thereof, and sodium-ion battery
CN116154138A
Positive pole piece, energy storage device and electric equipment
CN117059739A
Positive electrode material, sodium ion battery, and electric device
WO2024082817A1